Presepsin for pre-operative prediction of major adverse cardiovascular events in coronary heart disease patients undergoing noncardiac surgery: post hoc analysis of the Leukocytes and Cardiovascular Peri-operative Events-2 (LeukoCAPE-2) study - Handke, Jessica; Scholz, Anna; Dehne, Sarah; Krisam, Johannes; Gillmann, Hans-Jörg; Janßen, Henrike; Arens, Christoph; Espeter, Florian; Uhle, Florian; Motsch, Johann; Weigand, Markus A.; Larmann, Jan (European journal of anaesthesiology, 2020)
Background: Accurate pre-operative evaluation of cardiovascular risk is vital to identify patients at risk for major adverse cardiovascular and cerebrovascular events (MACCE) after noncardiac surgery. Elevated presepsin (sCD14-ST) is associated with peri-operative MACCE in coronary artery disease (CAD) patients after noncardiac surgery. - Objectives: Validating the prognostic utility of presepsin for MACCE after noncardiac surgery. - Design: Prospective patient enrolment and blood sampling, followed by post hoc evaluation of pre-operative presepsin for prediction of MACCE. - Setting: Single university centre. - Patients: A total of 222 CAD patients undergoing elective, inpatient noncardiac surgery. - Intervention: Pre-operative presepsin measurement. - Main outcome measures: MACCE (cardiovascular death, myocardial infarction, myocardial ischaemia and stroke) at 30 days postsurgery. - Results: MACCE was diagnosed in 23 (10%) patients. MACCE patients presented with increased pre-operative presepsin (median [IQR]; 212 [163 to 358] vs. 156 [102 to 273] pgml−1, P = 0.023). Presepsin exceeding the previously derived threshold of 184 pg ml−1 was associated with increased 30-day MACCE rate. After adjustment for confounders, presepsin more than 184 pg ml−1 [OR = 2.8 (95% confidence interval 1.1 to 7.3), P = 0.03] remained an independent predictor of peri-operative MACCE. Predictive accuracy of presepsin was moderate [area under the curve (AUC) = 0.65 (0.54 to 0.75), P = 0.023]. While the basic risk model of revised cardiac risk index, high-sensitive cardiac troponin T and N-terminal fragment of pro-brain natriuretic peptide resulted in an AUC = 0.62 (0.48 to 0.75), P = 0.072, addition of presepsin to the model led to an AUC = 0.67 (0.56 to 0.78), P = 0.009 and (ΔAUC = 0.05, P = 0.438). Additive risk predictive value of presepsin was demonstrated by integrated discrimination improvement analysis (integrated discrimination improvement = 0.023, P = 0.022). Net reclassification improvement revealed that the additional strength of presepsin was attributed to the reclassification of no-MACCE patients into a lower risk group. - Conclusion: Increased pre-operative presepsin independently predicted 30-day MACCE in CAD patients undergoing major noncardiac surgery. Complementing cardiovascular risk prediction by inflammatory biomarkers, such as presepsin, offers potential to improve peri-operative care. However, as prediction accuracy of presepsin was only moderate, further validation studies are needed